INDUCTION OF OVULATORY ESTRUS USING OVSYNCH PROTOCOL AND SUBSEQUENT FERTILITY IN TRUE ANESTRUS BUFFALO HEIFERS - GHUMAN, S P S; SINGH, JAGIR; HONPARKHE, M; DADARWAL, D (The Indian Journal of Animal Reproduction, 2023)
The aim of using Ovsynch protocol in true anestrus buffalo heifers (n=11) was to induce synchronizedovulatory estrus and thereafter, to assess the first service conception rate. 'Ovsynch' involvedadministration of a GnRH-analogue at days O and 9, and a PGF2alpha analogue on day 7. Transrectalovarian ultrasonography and jugular vein blood sampling was done daily starting from first-GnRH tillovulation after second-GnRH. Thereafter, these procedures were performed on days 5, 10, 15, 21 and42 post-ovulation. Heifers were inseminated on day 10 and if required on day 11. In response to firstGnRH,all the heifers ovulated (P
Keywords: Anestrus; Buffalo; Fertility; Ovsynch; Ovulation